Child Poverty Indicators: The Case of Elazig - Kılınç, Pelın; Yılmaz, Merve Sefa (Cenk AKSOY, 2023)
The fact that children are faced with all kinds of risk situations constitutes the background for considering them as one of the disadvantaged groups. One of these risk situations is poverty. This research is based on interviews with children and their parents (45 parents, 33 children) in the households living in the city center of Elazig (through SASA) designated as poor. In order to analyze better a special and disadvantageous issue such as child poverty, it is aimed to make an in-depth analysis of this issue. A qualitative research method was preferred for the study because it aimed to conduct interviews with poor individuals. In order to determine the universe and sample of the research, the snowball sampling technique, a sampling method, was used. The data in the study is a case study based on the analysis of the answers obtained from the form of the interview. The data of the study is based on in-depth interviews conducted with school-aged child and their parents. The obtained data were analyzed with quantitative (tables) and qualitative (interview notes) research techniques. Thus, it is aimed to determine the socioeconomic problems and needs of the poor children such as education, health, nutrition, and shelter, and to make a sociological analysis of them.